Components of metabolic syndrome increase the risk of mortality in nonalcoholic fatty liver disease (NAFLD). Issue 13 (March 2018) - Golabi, Pegah; Otgonsuren, Munkhzul; de Avila, Leyla; Sayiner, Mehmet; Rafiq, Nila; Younossi, Zobair M.
Abstract : Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in the United States. Metabolic syndrome (MS) components are highly prevalent in NAFLD. Our aim is to assess the relationship of NAFLD and MS with long-term outcome of mortality. The Third National Health and Nutrition Examination Survey (NHANES) was utilized. NAFLD was diagnosed by ultrasound in the presence of hepatic steatosis and no other causes of chronic liver disease. History of MS and its components were obtained from self-reported NHANES questionnaires. Mortality was obtained from Mortality-Linkage File, through December 31, 2011. Chi-square test was used for categorical variables and Cox proportional models estimated hazard ratios with 95% confidence interval. NAFLD cohort (n = 3613) had a median age of 43 years, 73% white, and 50% male. NAFLD group with at least one MS condition was significantly older, had higher body mass index, more likely to have insulin resistance, and heart disease compared to NAFLD group without MS. Over 19-years of follow-up, 1039 people died. Compared to NAFLD patients without MS, presence of one MS component increased the risk of mortality at 8-year (2.6% vs 4.7%) and 16-year (6% vs 11.9%) ( P < .001). After adjusting for socio-demographic factors, NAFLD with all MS components was associated with overall, cardiac and liver-mortality. Increased number of MS components was associated with lower survival ( P < .0001). Patients with NAFLD and MS have higher mortality risk compared to NAFLD patients without MS. These NAFLD patients should be prioritized for the development of treatment regimens.